Determining the size of retinal features : a study on the magnification of a fundus photograph and its application in the development of reaction time perimetry - Knaapi, Laura (fi=Turun yliopisto|en=University of Turku|, 2018)
Fundus photography plays a vital part in the diagnosis and follow-up of ocular pathology. Both the camera optics and the ametropia of the given eye influence the magnification of a fundus photograph. Determining the true size of retinal features thus requires the use of mathematical equations. This study was aimed at evaluating the formula of Bennett et al. (1994) for determining the size of retinal features in two different clinical settings. First, its use was verified with healthy volunteers by measuring the macula-disc center distance from fundus photographs taken with the telecentric Zeiss fundus camera, and by calculating the theoretical location of the blind spot based on the macula-disc center distance. These results were compared with the results from a visual field examination using the Octopus custom made Blind Spot visual field program. The theoretical location of the blind spot, derived from calculations based on fundus photography, corresponded to the visual field examination derived location of the physiological blind spot. In addition, the magnification characteristics of the Topcon fundus camera were assessed by calculating its conversion factor. Secondly, the accuracy of the formula was evaluated after cataract surgery and IOL implantation. Cataract surgery and IOL implantation did not have an effect of clinical significance on the magnification of a fundus photograph taken with the telecentric Zeiss and Topcon fundus cameras even after the ametropia and the anterior chamber depth were changed due to surgery. Thirdly, the use of the macula-disc center distance as a reference tool for determining the size of retinal features from fundus photographs was evaluated in prematurely born children aged from 10 to 11 years. The macula-disc center distance was found to be close to a constant. Lastly, a novel method for examining the visual field was introduced. Reaction time perimetry was shown to be able to detect the physiological blind spot. The location of the blind spot was verified with two independent methods: First, by calculating the theoretical location of the blind spot based on the macula-disc center distance derived from fundus photographs taken with the telecentric Zeiss fundus camera, and second, by visual field examination using the Octopus custom made Blind Spot visual field program. Validating the use of reaction time perimetry in different ocular pathology requires further studies.

Verkkokalvon rakenteiden koon määrittäminen silmänpohjan valokuvauksen avulla ja reaktio-aikaan perustuvan näkökenttätutkimuksen kehittäminen Silmänpohjan valokuvauksella on tärkeä merkitys silmänpohjan sairauksien seurannassa. Sekä kameran optiikalla että silmän taittovoimalla on vaikutus silmänpohjan valokuvan suurennokseen. Objektin todellisen koon määrittäminen silmänpohjan valokuvasta vaatii näin ollen matemaattisten kaavojen käyttöä. Tämän väitöskirjan tavoitteena oli tutkia Bennettin ym. vuonna 1994 kehittämää matemaattista kaavaa verkkokalvon rakenteiden koon arvioimiseksi. Kaavan käyttö verifioitiin käytännössä terveillä vapaaehtoisilla koehenkilöillä mittaamalla tarkan näön alueen ja näköhermon pään keskipisteiden välimatka silmänpohjan valokuvista, jotka oli otettu Zeissin telesentrisellä silmänpohjan valokuvauskameralla. Kuvien perusteella laskettiin sokean täplän teoreettinen sijainti. Saatujen tulosten todettiin vastaavan Octopusnäkökenttätutkimuksen avulla määritetyn fysiologisen sokean täplän sijaintia. Lisäksi tutkimuksessa laskettiin Topconin silmänpohjan valokuvauskameran muuntokerroin. Kaihileikkauksessa keinomykiön asentamisella aiheutetun silmän taittovoiman ja etukammion syvyyden muuttumisella ei todettu olevan kliinisesti merkittävää vaikutusta Zeissin telesentrisellä eikä Topconin silmänpohjan valokuvauskameralla otettujen silmänpohjan valokuvien suurennokseen. Tutkimuksessa selvitettiin myös keskosuuden vaikutusta tarkan näön alueen ja näköhermonpään keskipisteiden välimatkaan. Välimatkan todettiin olevan lähellä vakiota 10–11 -vuotiailla keskosena syntyneillä lapsilla. Näin ollen johtopäätöksenä oli, että sitä voitaisiin käyttää referenssinä keskosena syntyneillä henkilöillä, kun silmänpohjan valokuvasta halutaan määrittää objektin koko. Lopuksi tutkimuksessa esiteltiin uusi reaktioajan mittaukseen perustuva menetelmä, jonka avulla voidaan tutkia näkökenttää. Reaktioajan mittaukseen perustuvan näkökenttälaitteen todettiin löytävän sokean täplän terveillä vapaaehtoisilla. Tulos verifioitiin määrittämällä sokean täplän sijainti kahden muun menetelmän avulla: selvittämällä sen teoreettinen sijainti Zeissin silmänpohjan valokuvauskameralla otettujen silmänpohjan valokuvien perusteella ja tutkimalla fysiologisen sokean täplän sijainti Octopus-näkökenttätutkimuksen avulla. Reaktioajan mittaukseen perustuvan menetelmän soveltuvuus näkökentän tutkimiseen terveillä vapaaehtoisilla ja eri silmäsairauksien yhteydessä vaatii kuitenkin jatkotutkimuksia.